The Effect Of Physical Training in the Form of Walking on Blood Pressure Reduction and the Quality of Life of the Elderly Living With Hypertension - Bakar, Abu; Widyastuti, Nanik; Hidayati, Laily; Qomariah, Siti Nur (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the effects of physical exercise in the form of walking on systolic blood pressure, diastolic blood pressure and the quality of life of the elderly with hypertension. Hypertension is called a silent killer because the disease causes death. Hypertension affects the quality of life of the elderly in terms of their physical health, psychological condition, social relations and environmental condition. The study design used was quasi-experimental. The sample involved consisted of 27 respondents in the intervention group and 27 respondents in the control group. The independent variable in this study was physical exercise on foot and the dependent variables were blood pressure and quality of life. The instruments used were an aneroid tensimeter, a stethoscope and a questionnaire. Analysis was done using the Wilcoxon Signed Rank Test and the Mann Whitney test with a significance level α ≤ 0.05. Physical exercise on foot significantly impacted systolic blood pressure (p = 0,000), diastolic blood pressure (p = 0.001) and quality of life in terms of physical health (p = 0.014), psychological condition (p = 0,000), social relations (p = 0,000) p = 0,000) and the environmental conditions (p = 0,000). The walking exercise has positive benefits when it comes to overcoming the problem of blood pressure and improving the quality of life of hypertensive patients. For further research, the researchers suggest carrying out physical exercise in the form of walking at different intensities and paying attention to confounding factors for hypertension.